An examination of the literature relating to issues affecting how companies manage through measures - Franco-Santos, Monica; Bourne, Mike (Taylor & Francis, 2005)
In the last decade, organizations have devoted enormous time and effort to the development of business performance measurement (BPM) systems. Many articles have been written on how to design and implement these types of systems. However, few studies have addressed the issue of why some organizations are better able to 'manage through measures' than others. In other words, why do some organizations struggle to ensure that action follows measurement, whilst others systematically use their metrics to inform their decision-making processes, and their subsequent actions? This paper aims to contribute to a more complete understanding of the use of BPM systems by reviewing the performance measurement literature developed in the management arena. It differs from previous examinations of performance measurement and management control systems in that it uses a broader scope and follows a new method of literature review applied to management research, namely, systematic review. The paper focuses on the thematic analysis of the review only. The insights extracted from the literature are articulated and presented in a management framework. In addition, the paper identifies different gaps in the literature that require further research.
Keywords: Performance measurement systems; Performance measurement; Performance measures